WATER RELATIONS IN LETTUCE(Lactuca sativa L.Var longiflia) - Caser G. Abdel (Mesopotamia Journal of Agriculture)
Four experiments were conducted to investigate sowing rates (1, 2, 3, or 4g. seeds.mˉ²) effects on lettuce transplant performance, to improve growth and yield of lettuce by populations, plot and furrow cultivations under rainfalls and supplementary irrigation, to boost drought resistance by using either GA3 or NAA rates of 0, 50, 75 or 100 mg.lˉ1. Results of experiment 1 showed that 2 g seeds.mˉ² was the most suitable rate for the high performance transplant productions. It gave transplant numbers of 738.3 in which large, medium and small size transplants constituted 18, 36, and 46%, respectively. Results of experiment 2 revealed that the possibility of producing lettuce under rainfalls only and supplementary irrigation is not required, furrow cultivation was superior to that of plot. It exceeded the latter by 15.4% in term of yield, high population (28 plants.mˉ²) yielded ( 109.1% ) more than that of ( 14 plnt.mˉ²),however it tended to reduce the weight of individual head. The highest yield ( 8.08 kg.mˉ²) was obtained from furrow high population interactions with either rainfalls or supplementary irrigation. Experiment 3 results confirmed that GA3 highly improved the hearting process, particularly 100mg.l-1 treatment which resulted in the highest yield(5.9 kg.mˉ²), bulk density ( 0.2 g.cmˉ³), head size(2150 cm³) and individual head weight (423.3 g). The final experiment 4 results showed that NAA rate of 50 mg.lˉ1 was the most effective treatment as it gave the highest yield ( 3.12 kg.mˉ²), and weight of single head (403.3 g). However NAA rates were inferior to these of GA3.